Effects of Permissive Hypercapnia on Laparoscopic Surgery for Rectal Carcinoma - Lei Wang; Lina Yang; Jing Yang; Shiqiang Shan (Gastroenterology Research and Practice)
Background. Permissive hypercapnia has been recommended during the treatment of chronic diseases; however, there are insufficient clinical data to investigate the feasibility of permissive hypercapnia in relatively long-term surgeries such as laparoscopic surgery for rectal carcinoma. This prospective study is aimed at investigating the efficacy and safety of permissive hypercapnia under different CO2 pneumoperitoneum pressures during the laparoscopic surgery for rectal carcinoma. Methods. A total of 90 patients undergoing laparoscopic surgery for rectal carcinoma were recruited from July 2016 to March 2017. They were randomly assigned to high hypercapnia group (n=30), low hypercapnia group (n=30), or control group (n=30), whose PaCO2 levels were maintained at 56-65 mmHg, 46-55 mmHg, or 35-45 mmHg, respectively. The primary endpoint was peak pressure. Plateau pressure, dynamic compliance, arterial blood analysis, and hemodynamic measures were collected as secondary outcomes. Adverse events were monitored. Results. High hypercapnia group were reported to be associated with significantly lower peak pressure and plateau pressure, but higher dynamic compliance compared to low hypercapnia and control group (all P<0.01). Moreover, patients in the high hypercapnia group had higher postoperation oxygenation index values compared to those in the low hypercapnia and control group (all P<0.01). There is no significant difference in the pH, Spo2, MAP, heart rate, and adverse events among the three groups. Conclusion. Permissive hypercapnia with a PaCO2 level of 56-65 mmHg was able to improve respiratory function after laparoscopic surgery in rectal cancer patients.